2019
DOI: 10.2134/cs2019.52.0601
|View full text |Cite
|
Sign up to set email alerts
|

Determining the optimum irrigation schedule in furrow‐irrigated cotton using soil moisture sensors

Abstract: The Mississippi River Valley Alluvial Aquifer is declining at a rapid rate due to withdrawal for agricultural irrigation. This research was conducted to develop a sensor‐based irrigation threshold for cotton that maximizes net returns and irrigation water use efficiency. Earn 1 CEU in Soil & Water Management by reading this article and taking the quiz at http://www.certifiedcropadviser.org/education/classroom/classes/727.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Irrigations were scheduled based on a soil‐matric potential of about −90 kPa at 60 cm soil depths in the FI irrigation plots as recommended by Plumblee et al. (2019). In 2018, a total of 220 mm of irrigation was applied in the FI treatments in four irrigation events of 55 mm each applied through every furrow on 15 May, 20 June, 6 July, and 3 August, while the HI treatments received about half the amount of water on the same dates but in every other furrow, amounting to total water applied of about 115 vs 220 mm in the FI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Irrigations were scheduled based on a soil‐matric potential of about −90 kPa at 60 cm soil depths in the FI irrigation plots as recommended by Plumblee et al. (2019). In 2018, a total of 220 mm of irrigation was applied in the FI treatments in four irrigation events of 55 mm each applied through every furrow on 15 May, 20 June, 6 July, and 3 August, while the HI treatments received about half the amount of water on the same dates but in every other furrow, amounting to total water applied of about 115 vs 220 mm in the FI.…”
Section: Methodsmentioning
confidence: 99%
“…In an attempt to fill this gap in scientific research in the Mississippi Delta region, Plumblee et al. (2019) reported an increase in IWUE in cotton ( Gossypium L.) of 61% after adopting an irrigation schedule that triggered irrigations at −90 kPa matric water potential in 100‐cm soil depth. Although the physiological and agronomic advantages of a TR soybean production system compared with an SR system have been thoroughly researched, no information on the IWUE of a TR over an SR planting geometry was reported for the Mississippi Delta (Plumblee et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of scientific research that enhances irrigation water use efficiency (WUE) was attributed as one of the primary reasons for the depletion (Clark et al, 2011). Plumblee et al (2019) reported an increase in WUE by 61% by adopting a matric water potential sensor-based irrigation at -90 kPa average in a 100-cm soil depth in MS Delta. Pettigrew and Zeng (2014) reported a 25% increase weeds, followed by disc-tillage to generate furrows and ridges (102-cm row spacing) for planting cotton seeds and facilitating furrow irrigations.…”
Section: Methodsmentioning
confidence: 99%
“…Sensors for measuring soil-matrix water potential (Watermark sensors, Irrometer Company, Inc, Riverside, CA USA) were installed at soil depths of 15, 30, and 60 cm in selected representative plots. Irrigations were scheduled based on a soil matrix potential of about − 90 kPa at 45 cm soil depths, as recommended by Plumblee et al (2019). The amount of irrigation water applied during each season in each plot was measured using a ow meter.…”
Section: Cultural Practicesmentioning
confidence: 99%